Immunological Alterations due to Hemodialysis Might Interfere with Early Complications in Renal Transplantation - Kristin Mai; Andreas Boldt; Hans-Michael Hau; Michael Kirschfink; Stephan Schiekofer; Frieder Keller; Joachim Beige; Athanassios Giannis; Ulrich Sack; Franz Maximilian Rasche (Analytical Cellular Pathology)
Background. Chronic or intercurrent alterations of the immune system in patients with end-stage renal disease (CKD) and intermittent hemodialysis (CKD5D, HD) have been attributed to an acute rejection of renal allograft. Methods. Leukocyte subsets in flow cytometry, complement activation, and concentrations of TGFβ, sCD30 (ELISA), and interleukins (CBA) of fifteen patients eligible for renal transplantation were analyzed before, during, and after a regular HD. Results. Before HD, the median proportion of CD8+ effector cells, CD8+ CCR5+ effector cells, and HLA-DR+ regulatory T cells as well as the median concentration of soluble CD30 increased and naive CD8+ T cells decreased. During HD, there was a significant decrease in CD4- CD8- T cells (p<0.001) and an increase in CD25+ T cells (p=0.026), sCD30 (p<0.001), HLA-DR+ regulatory T cells (p=0.005), and regulatory T cells (p=0.003). TGFβ and sCD30 increased significantly over time. The activity of the classical complement pathway started to slightly increase after the first hour of HD and lasted until fifteen minutes after finishing dialysis. The decrease in the functional activity of the alternative pathway was only transient and was followed by a significant increase within 15 minutes after finishing the treatment. Conclusion. HD might interact with the allograft outcome by influencing T cell subsets and activation of the complement system in a biphasic course.